Multiscale mathematical modelling of drug activation by co-grinding. (14th December 2022) - Grassi, Mario; Colombo, Italo; Manca, Davide; Biasin, Alice; Grassi, Lucia; Grassi, Gabriele; Abrami, Michela
Highlights: Nanonization improves the solubility of poorly water soluble drugs. Nanonization often implies recurring to co-grinding. A multiscale mathematical modelling of co-grinding was developed. The developed mathematical (MM) model can interpret the experimental data. MM is the rationale connection between mill set-up and co-ground drug properties. Abstract: Since the 1980s, drug activation by grinding or co-grinding has evolved considerably, allowing the conversion of microcrystals into nanocrystals or amorphous phases, whose increased solubility brings a significant improvement in drug bioavailability. This has prompted many researchers to investigate and understand the entire grinding/co-grinding process. Therefore, the present work focuses on the multiscale mathematical modelling of these three aspects to establish a rational relationship between the mill setting and the properties of the milled drug. Based on the developed model, it was possible to correctly interpret and describe the experimental data obtained when we ground two poorly water-soluble drugs (nifedipine and nimesulide) with a stabiliser (cross-linked polymer; polyvinylpyrrolidone) in two mills (vibrational and planetary mills). Interestingly, despite the complexity of the whole phenomenon, the implementation of the model only required the use of a Microsoft Excel sheet in which a suitable user-defined function was embedded.